¬Sistem Dokumentasi Kurikulum, Penawaran Mata Kuliah, dan Alokasi Dosen Pengajar (Studi Kasus Fakultas Teknologi Informasi Universitas Tarumanagara) - Stevy Lie; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
System of curriculum management, class offers, and allocation of lecturers is made by using Naive Bayes to produce curriculum data, class offers, and allocation of a class lecturer. The sample case is Faculty of Information Technology at Tarumanagara University. Naive Bayes is used to acquire class opened and the number of classes that need to be offered in the new semester. The test results show has success to do manufacturing system, however can only offer per class. Kata KunciAlokasi Dosen Pengajar, Fakultas Teknologi Informasi Universitas Tarumanagara, Naive Bayes, Penawaran Mata Kuliah, Dokumentasi Kurikulum